Lesions in the Skin of Cattle Associated to Hairy Vetch Consumption (Vicia villosa) - Silveira, Amaro Francisco Viero; Panziera, Welden; Sousa, Susy Hermes de; Cecco, Bianca Santana; Schwertz, Claiton Ismael; Gava, Aldo; Driemeier, David; Sonne, Luciana (Acta Scientiae Veterinariae, 2017)
Background: Hairy vetch (Vicia spp.) is a high-protein source forage to cattle. The poisoning is clinically characterized by a systemic granulomatous disease, which causes dermatitis, diarrhea, decreased milk production and weight loss. The specie of hairy vetch related to systemic granulomatous disease in cattle is Vicia villosa. This work aims to describe the epidemiological, clinical, gross, microscopic and immunohistochemistry features of the skin lesions caused by the consumption of V. villosa in cattle affected by the systemic granulomatous disease. Materials, Methods & Results: A retrospective study of necropsy and biopsy exams performed between the period of 2005-2016 aiming for cattle with systemic granulomatous disease after consumption of hairy vetch was carried out in the archives of the Setor de Patologia Veterinária from the UFRGS. Epidemiological data included the sex, age, and breed of the animals affected. Gross and microscopical lesions, in addition to the immunohistochemistry anti-T lymphocytes (CD3), anti-B lymphocytes (CD79a), and anti-macrophages (CD68) features, were evaluated. The histological lesions and immunohistochemistry staining were quantified in mild (+), moderate (++), and severe (+++). The diagnosis of systemic granulomatous disease with skin lesions after consumption of Vicia villosa was observed in eight cattle. All animals were females, with 5-8 year-old (average 6.6 years), Holstein Friesian cattle (7) and Jersey (1) breeds. These cattle had a clinical history of severe pruritus, anorexia, apathy, decreased milk production, weight loss, and hyperthermia. Grossly, lesions were characterized by alopecia (8/8), crusts (7/8), lichenification and seborrhea (2/8), and exudative lesions (2/8), and involved the head (7/8), limbs (5/8), neck (4/8), trunk (4/8), perineum area (3/8), udder (3/8), and tail (3/8). Histology revealed a mild to moderate inflammatory infiltrate (7/7), composed by lymphocytes (7/7), macrophages (7/7), occasional eosinophils, and rare multinucleated giant cells (1/7). It was also classified in mild to severe perivascular dermatitis (7/7), mild to moderate perifolliculitis (4/7), superficial dermatitis (3/7), moderate to severe mural folliculitis (2/7), and hidradenitis (1/7). Another findings were moderate apocrine sweat gland ectasia, mild to moderate orthokeratotic hyperkeratosis, mild to moderate spongiosis, mild to moderate acanthosis, mild to severe serocellular crusts, mild pigmentary incontinence, mild to severe Munro’s microabscesses, mild to moderate hydropic degeneration, apoptosis, ulcers, mild to moderate superficial edema of the dermis, variable epitheliotropism and erosions. Immunohistochemistry of all skin sections had mild to severe staining for T cell (CD3), mild staining for macrophages (CD68), and immunostaining was rare (4/7) or absent (3/7) for B cells (CD79a). Discussion: Cutaneous lesions observed in this study were similar to those previously described by other authors for this condition, and were characterized by focal to coalescent areas of alopecia, lichenification and seborrhea, associated clinically to a severe pruritus. Histologically, these consisted of perivascular dermatitis, and perifolliculitis with an inflammatory infiltrate composed predominantly by lymphocytes, macrophages, with occasional eosinophils and multinucleated giant cells. Immunohistochemistry demonstrates a marked immunostaining for T cells, while it was mild for macrophages, which reinforces the involvement of the delayed type hypersensitivity (type IV) reaction in the pathogenesis of the disease.